Increased Heat Transport in Ultra-hot Jupiter Atmospheres through H2 Dissociation and Recombination - Bell, Taylor J.; Cowan, Nicolas B. (Astrophysical journal. Letters, 2018)
A new class of exoplanets is beginning to emerge: planets with dayside atmospheres that resemble stellar atmospheres as most of their molecular constituents dissociate. The effects of the dissociation of these species will be varied and must be carefully accounted for. Here we take the first steps toward understanding the consequences of dissociation and recombination of molecular hydrogen (H2) on atmospheric heat recirculation. Using a simple energy balance model with eastward winds, we demonstrate that H2 dissociation/recombination can significantly increase the day-night heat transport on ultra-hot Jupiters (UHJs): gas giant exoplanets where significant H2 dissociation occurs. The atomic hydrogen from the highly irradiated daysides of UHJs will transport some of the energy deposited on the dayside toward the nightside of the planet where the H atoms recombine into H2; this mechanism bears similarities to latent heat. Given a fixed wind speed, this will act to increase the heat recirculation efficiency; alternatively, a measured heat recirculation efficiency will require slower wind speeds after accounting for H2 dissociation/recombination.